2019
DOI: 10.3906/bot-1812-12
|View full text |Cite
|
Sign up to set email alerts
|

Forage pea (Pisumsativum var. arvense L.) landraces reveal morphological andgenetic diversities

Abstract: The objective of this study was to assess morphological and genetic diversities of 48 forage pea landraces collected from different locations at different altitudes in Turkey. Morphological, quality, and yield features were determined for the landraces and three control cultivars in three subsequent years. Genetic diversities of the landraces and cultivars were also monitored using microsatellite (SSR) markers. Our results revealed that the features of landraces are significantly different. The hay weights and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
2
6
1
Order By: Relevance
“…While no change was observed in ADF and NDF in P1 and P4 (Figure 3, 4), P2, and P3 showed increases under stress condition. Increased ADF rates decreases the forage quality due to the increase of the nondigestible fiber content (Demirkol and Yilmaz, 2019). Similar decreases in crude protein ratio and forage quality under phosphate limited conditions were reported in phosphate-sensitive narbon vetch (Turk et al, 2007).…”
Section: Yield and Quality Parameterssupporting
confidence: 66%
“…While no change was observed in ADF and NDF in P1 and P4 (Figure 3, 4), P2, and P3 showed increases under stress condition. Increased ADF rates decreases the forage quality due to the increase of the nondigestible fiber content (Demirkol and Yilmaz, 2019). Similar decreases in crude protein ratio and forage quality under phosphate limited conditions were reported in phosphate-sensitive narbon vetch (Turk et al, 2007).…”
Section: Yield and Quality Parameterssupporting
confidence: 66%
“…Our results demonstrated that there was an enormous variation in the available forage pea genotypes. In Turkey, forage pea genotypes collected from North East Anatolia and Eastern Black Sea regions indicated immense variation regarding agro-morphological characteristics similar to these findings (Tan et al, 2012;Tan et al, 2013;Demirkol and Yılmaz, 2019). Plant heights and dry matter yields of forage pea genotypes ranged from 68.8 to 102 cm and 486 to 677 kg/da, respectively according to Tan et al (2013).…”
Section: Resultsmentioning
confidence: 57%
“…Morphological characterization is the first step in the identification and classification of germplasm (Smith & Smith, 1989). In the studies conducted by, Tan et al (2012), Tan et al (2013) and Demirkol and Yılmaz (2019) compared forage pea genotypes collected from different locations with commercial varieties to identify promising local ecotypes, there were important differences between the genotypes in terms of the agro-morphological characters. Ali et al (2007), Nisar et al (2008), Gatti et al (2011), Nisar et al (2011 and Umar et al (2014) found that the genetic diversity in peas and their relationship with the yield components were mostly based on agromorphological characters.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Demirkol and Yilmaz [ 15 ] studied the genetic diversity of 48 forage pea landraces collected from the East Black Sea Region in Turkey. Forage pea landraces were collected using the criteria of the International Union for the Protection of New Varieties of Plants (UPOV) and used 32 SSR markers.…”
Section: Introductionmentioning
confidence: 99%